Technological Change and the Future of Warfare - O'Hanlon, Michael (Rawalpindi, Pakistan Army Education Publishing House, 2005)
Many defence analysts have posited that we are on the threshold of a technological revolution in military affairs. This book offers a more restrained view of the future of warfare.
Include Graph and Index
Keywords: Military policy -- United States -- Military art and science--Technological innovations